PENGARUH PENGGUNAAN PARASETAMOL SELAMA KEHAMILAN TERHADAP PREEKLAMPSIA - Dita Maria Virginia (Sanata Dharma University, 2013)
Abstract: Preeclampsia is one of the causes of maternal death. The important factor ofpreeclampsia's pathophysiology is reduction of PGI2 as vasodilator. It causes vasoconstrictionwhich influences the formation of desidua. Paracetamol is the most widely used antipyretic in theworld. Mechanism of action of paracetamol may lead to preeclampsia. The aim of this researchwas to determine the relation between paracetamol used during pregnancy and preeclampsia inRS X Yogyakarta. The research was an analytical epidemiology with case control study design.Data were obtained from medical record and interview. Sample size was 137 maternal patients inOctober-December 2013 and 72 maternal have been followed up. Data were analyzed usingdescriptive statistics, Chi-square tests, and logistic regression. Preeclampsia patients weretaking paracetamol during pregnancy (71.8%), aged 30-40 years (84.6%), and hadpreeclampsia family history (28.2) than non preeclampsia patient. Chi-square test showed therelation between paracetamol used (p=0.010, OR= 3.46 (95%CI= 1.30 9.22), dose a day(p=0.010, OR= 3.18 (95%CI= 1.12 9.06), duration of paracetamol used (p=0.005, OR= 7.75(95%CI= 1.60 37.53), and used within first trimester (p=0.878, OR= 0.91 (95%CI= 0.26 3.12) to preeclampsia. Logistic regression analyses showed no correlation between variables topreeclampsia. Women who used paracetamol during pregnancy had an increased risk ofpreeclampsia.Key words: preeclampsia, paracetamol, pregnancy.